2020
DOI: 10.12820/rbafs.25e0143
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, sedentary behavior and physical activity: changes on children’s routine during the COVID-19

Abstract: Social isolation was adopted as a strategy to reduce the transmission speed of the severe acute respiratory syndrome of coronavirus 2 (SARS-CoV-2) in several countries in the world, including Brazil. As a result, schools were closed and the routines of children altered, affecting sleep, sedentary behavior, and physical activity. The present study aims to compare the children’s weekly routine and time spent on sleep, sedentary behavior and physical activity before and during the Coronavirus disease 2019 (COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
6
0
6
Order By: Relevance
“…Thus, previous studies have shown that questionnaires are adequate resources for monitoring indicators related to fitness, physical activity, and health in children in social distancing context, mainly in lockdown [ 17 , 18 , 25 , 26 ]. Some cross-sectional diagnoses were made indicating that sedentary behavior, low levels of physical activity, and low levels of physical fitness were evident [ 14 , 17 , 18 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, previous studies have shown that questionnaires are adequate resources for monitoring indicators related to fitness, physical activity, and health in children in social distancing context, mainly in lockdown [ 17 , 18 , 25 , 26 ]. Some cross-sectional diagnoses were made indicating that sedentary behavior, low levels of physical activity, and low levels of physical fitness were evident [ 14 , 17 , 18 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diversas questões estão interrelacionadas: o aumento do tempo total de tela talvez relacionado à diminuição das possibilidades de brincar, embora relacionada ao fechamento de escolas, também ocorre em decorrência da falta de espaço adequado para as crianças que não podem sair de casa (Silva et al, 2020).…”
Section: Discussionunclassified
“…Além de prevenir essas comorbidades, a prática de exercícios físicos é um fator protetor para reduzir os problemas comportamentais de crianças em idade escolar em distanciamento social. Fazer atividade física tem o potencial de reduzir os sintomas de hiperatividade-desatenção e problemas de comportamento em criança (Silva et al, 2020).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…al (2017), a acessibilidade a internet vem se expandido com velocidade no Brasil, potencializando facilidades como de acesso à informação, inserção social, compras, educação entre outras, como também expondo crianças e adolescentes à riscos, como o acesso à conteúdos inapropriados a faixa etária, priorização por relacionamentos virtuais, bullying e assédio sexual. Desta forma, conforme Silva et. al (2020), a situação imposta pela pandemia do COVID-19, impôs a suspensão das aulas presenciais, consequentemente uma redução do deslocamento ativo e isolamento social, criando uma mudança na rotina diária dos alunos, resultando em um significativo aumento do período de permanência em celulares, computadores e televisão.…”
Section: Introductionunclassified